Prescribing and documentation by critical care clinical pharmacy specialists with around‐the‐clock staffing: A single‐center evaluation. Issue 4 (20th January 2021) - Westmoreland, Kearsten; Bovio Franck, Jessica; Franck, Andrew J.
Abstract: Introduction: Evidence supports pharmacists as essential team members in the intensive care unit (ICU). Data are limited for pharmacist prescribing and documentation, ideal pharmacist staffing, and timing of clinical pharmacy activities in the ICU. Objective: The purpose of this evaluation was to assess the frequency, timing, and most common areas of prescribing and documentation for critical care clinical pharmacy specialists (CPSs) in a single medical center with around‐the‐clock staffing. Methods: A Veterans Affairs (VA) medical center implemented a collaborative practice model in which CPSs provide direct ICU patient care around the clock. Direct patient care activities are provided for two ICUs with three multidisciplinary teams (medical, surgical, and cardiovascular), the nutrition support team, and emergency response teams. Documentation through an electronic health record progress note is required any time a CPS performs a patient encounter and uses prescriptive authority. A retrospective evaluation was performed to evaluate critical care CPS patient encounters and clinical interventions from October 1, 2016 through September 30, 2020. Results: Cumulatively, 78 622 CPS clinical interventions requiring prescriptive authority were made during 17 938 documented encounters. For clinical interventions, 40 897 (52.0%) were during daytime hours and 37 725 (48.0%) were after‐hours. Of the documented encounters, 10 461 (58.3%) were during daytime hours compared with 7477 (41.7%) after‐hours. Medication‐related prescribing interventions accounted for 57 400 (73.0%) of the interventions, while 6931 (8.8%) were nonpharmacologic and 14 291 (18.2%) were additional interventions. The most common disease states for prescribing interventions included Anticoagulation (13.8%), Infectious Diseases (13.1%), Cardiovascular (10.5%), Nutrition/Gastrointestinal (6.6%), Neuropsychiatric (5.3%), Endocrine (4.3%), Nephrology (3.5%), and Pulmonary (1%). Conclusion: This evaluation provides details of prescribing and documentation by critical care CPSs with an around‐the‐clock staffing model. This may be useful for ICU clinicians and administrators considering expanding critical care pharmacy services.